IMPLEMNTASI METODE PENEMUAN TERBIMBING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR DI KECAMATAN TAMALATE KOTA MAKASSAR - Novita Dwi Maharani Sabban (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The low understanding of concepts and students' critical thinking skills is a crucial problem in mathematics learning. To solve this problem, there needs to be an innovative learning method and can activate students in the classroom. One method that can be done is to apply guided discovery methods. The purpose of this study was to determine the impact of mathematics learning with guided discovery methods on the ability to understand concepts and the ability to think critically of elementary school students. This study uses experimental design using a control group. The study subjects involved 104 elementary school students in Tamalate District, Makassar City, which consisted of three levels of school, namely high, medium and low levels. The instrument of data collection was in the form of test questions on the ability to understand concepts and the ability to think critically, observation sheets, attitude scale questionnaires and interview guidelines. From the discussion of research results, after applying mathematics learning with guided discovery methods it is known that understanding the concepts and critical thinking abilities of students who take learning with guided discovery methods is better in improving students' understanding of concepts and critical thinking skills at high, medium and low school level. In addition, most students showed a positive attitude towards mathematics learning with guided discovery methods. Based on research findings, mathematics learning with guided discovery methods is very potential to be applied in the field in an effort to improve the quality of education.